2005
DOI: 10.1093/biomet/92.3.519
|View full text |Cite
|
Sign up to set email alerts
|

A note on composite likelihood inference and model selection

Abstract: A composite likelihood consists in a combination of valid likelihood objects, usually related to small subsets of data. The merit of composite likelihood is to reduce the computational complexity so that it is possible to deal with large datasets and very complex models, even when the use of standard likelihood or Bayesian methods is not feasible. In this paper, we aim to suggest an integrated, general approach to inference and model selection using composite likelihood methods. In particular, we introduce an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
245
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(248 citation statements)
references
References 35 publications
3
245
0
Order By: Relevance
“…Based on the results of Varin & Vidoni (2005), the Akaike PML information criterion, AIC P L , is defined as:…”
Section: Pairwise Likelihood Model Selection Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of Varin & Vidoni (2005), the Akaike PML information criterion, AIC P L , is defined as:…”
Section: Pairwise Likelihood Model Selection Criteriamentioning
confidence: 99%
“…Pace et al (2011) present a Wald test, score test, and adjusted likelihood ratio test statistic for testing the hypothesis that a subset of parameters is equal to a specific value. Moreover, the model selection criteria AIC and the BIC are appropriately adjusted to hold under CL (Gao & Song, 2010;Varin et al, 2011;Varin & Vidoni, 2005). CL has gained attention because of its low computational complexity, which is not affected by model size.…”
Section: Introductionmentioning
confidence: 99%
“…Some clear grounds for not selecting linear regressions as descriptors of complexity in datasets is defined within the same analysis (R 2 value), which at low values implies a low explanatory power of the observed variance in the dependent variable by the dependent (Bevington et al 1993, Varin & Vidoni 2005. Another reason why linear regression cannot fits the data significantly corresponds to the assumption that the independent variable has been properly defined and that the experimental error and biological variability affects only the values of the dependent variable, which in a pragmatic sense never occurs (Bates & Watts 1988).…”
Section: Methodsmentioning
confidence: 99%
“…Further, the results indicated that for all variable specifications, the best spatial weight matrix specification was consistently the inverse of the continuous distance specification with the 0.25 mile distance band. This determination was based on the composite likelihood information criterion (CLIC) statistic, which may be used to compare the data fit of non-nested formulations (see Varin and Vidoni, 2005). This CLIC statistic takes the form shown below:…”
Section: Model Selection and Variable Specificationmentioning
confidence: 99%